Rejuvenation of creep resistance of a Ni-base single-crystal superalloy by hot isostatic pressing. (15th November 2017) - Ruttert, Benjamin; Bürger, David; Roncery, Lais Mujica; Parsa, Alireza Basir; Wollgramm, Philip; Eggeler, Gunther; Theisen, Werner
Highlights: A single specimen is exposed to a creep-rejuvenation-creep test cycle. A hot isostatic press providing fast quenching rates is used for rejuvenation. Microstructural evolution before and after creep as well as, rejuvenation are studied. Focus is on the γ/γ′-microstructure, pores, dislocations, and recrystallization. The impact of rejuvenation on additional creep life is evaluated. Graphical abstract: Abstract: Ni-base single-crystal turbine blades are exposed to a combination of high temperatures and high stresses during their service life in high-pressure turbines of aero engines or stationary gas turbines. This unavoidably leads to various internal microstructural changes such as rafting and the formation of cavities. This study introduces a creep-rejuvenation-creep test cycle using one miniature Ni-base single-crystal creep specimen. A novel hot isostatic press providing high quenching rates was applied to rejuvenate the damaged microstructure of the specimen after the first high-temperature creep degradation before the same specimen was repeatedly creep-tested under the same initial creep conditions. After rejuvenating, microstructural results obtained from high-resolution microscopy prove that the creep cavities were closed, dislocation densities were re-set, and the original but now slightly finer γ/γ′-microstructure was restored without any recrystallization. The subsequent creep test of the rejuvenated specimen demonstrated that the proposed rejuvenation procedure in this work is a suitable method to reproduce the initial creep behavior and to thus prolong the lifetime of an already crept Ni-base single-crystal specimen.